Efektivitas Penerapan Model Interaktif Terhadap Hasil Belajar IPA Siswa Kelas V UPT SPF SD Inpres Barombong III Kota Makassar - Sri Kurnia Rahayu; Syamsul Alam; Waddi Fatimah; Cayati Cayati (STKIP Andi Matappa Pangkep, 2022)
This research aimed to determine the effectiveness of the application of the interactive model on the science learning outcomes of V class UPT SPF SD Inpres Barombong III Kota Makassar City. The population in this research, namely class VA and VB consisted of 48 students and the samples in this research were all students of class VA SD Inpres Barombong III Kota Makassar city, which consisted of 24 students, the total number of samples used 24 students with simple random sampling technique. The instruments used students’ activity observation sheets, tests and questionnaires. As well as data collection techniques, namely observation sheets, tests, and questionnaires. The results of this research by using descriptive statistical analysis, the average value of the interactive model was 82 in the good category and the value of science learning outcomes was 82.29 in the category. Inferential statistical analysis, the results of the normality test Pretest 0.97 and Posttest 203 > 0.05, the homogeneity test result was 408 > 0.05 (homogeneous), the results of the hypothesis test showed the value of sig 0.00 with criteria Sig (0.00) > a (0.05).